Thailand Diabetes Registry Project: Glycemic control in Thai type 2 diabetes and its relation to hypoglycemic agent usage - Natapong Kosachunhanun (2018)
Objective: To determine the pattern of hyperglycemic agent usage in Thai type 2 diabetics (T2 DM) who attended the diabetes clinic in university and tertiary-care hospitals. The achievement of target glycemic control by various modalities of treatment was also analyzed. Material and Method: A cross-sectional, hospital-based diabetes registry of 8,913 type 2 diabetic patients in 11 tertiary care hospitals and medical schools was carried out from April to December 2003. Demographic data, usage of hypoglycemic agents and level of glycemic control were collected to determine the pattern of use, associated factors, and achievement of glycemic control. Results: Overall, 2,342(26.3%) of T2 DM achieved HbA1C less than 7%. The percentage of patients treated with metformin was 70.8%, sulfonylureas (SU) was 68.7% and insulin was 25.3%. Only 7.0% of patients received alpha-Glucosidase Inhibitor (AGI), 5.7% received ThaiZoliDinediones (TZD), 1.1% received repaglinide, and 3.2% was on diet control alone. Target glycemic control was achieved in 57.6%, 37.1%, 52%, 16.7%, 62.5%, 52% and 16.9% of patients who were on diet control only, monotherapy with SU,metformin, TZD, AGI, repaglinide and insulin,respectively. Sulfonylureas were the most commonly used drug for monotherapy. Metformin with sulfonylurea was the most common combination therapy and was used in 39.5% of patients. More than 60% of the patients treated with metformin monotherapy had body mass index (BMI) of more than 25 kg/m2, as compare to less than half of patient treated with other monotherapy agent. Mean duration of diabetes in the patients treated with metformin alone was 5.9 ± 5.5 years, less than that in the SU- treated patients (8.3 ±7.1 years) and also in the insulin-treated patients (14.8 ± 9.0 years). TDZ were commonly prescribed in combination with sulfonylureas and metformin in subjects with relatively longer duration of diabetes. Conclusion: Better treatment strategies for glucose control of diabetic patients on medical treatments should be encouraged to improve glycemic control and reduce long term complications.